Respuesta :
For this case we have the following polynomial:
[tex]x^2 - \frac{1}{4}x + k [/tex]
We suppose that we have a standard equation of the form:
[tex]ax ^ 2 + bx + c [/tex]
To make a perfect square trinomial, we need to complete the square.
Therefore, the value of c is:
[tex]c = (\frac{b}{2})^2 [/tex]
Using this definition for this case, we have:
[tex]k = (\frac{\frac{-1}{4}}{2})^2[/tex]
[tex]k= ( \frac{-1}{8} )^2[/tex]
[tex]k = \frac{1}{64} [/tex]
Therefore, the perfect square trinomial is:
[tex]x^2 - \frac{1}{4}x + \frac{1}{64} [/tex]
Answer:
The value of k is:
[tex]k = \frac{1}{64} [/tex]
[tex]x^2 - \frac{1}{4}x + k [/tex]
We suppose that we have a standard equation of the form:
[tex]ax ^ 2 + bx + c [/tex]
To make a perfect square trinomial, we need to complete the square.
Therefore, the value of c is:
[tex]c = (\frac{b}{2})^2 [/tex]
Using this definition for this case, we have:
[tex]k = (\frac{\frac{-1}{4}}{2})^2[/tex]
[tex]k= ( \frac{-1}{8} )^2[/tex]
[tex]k = \frac{1}{64} [/tex]
Therefore, the perfect square trinomial is:
[tex]x^2 - \frac{1}{4}x + \frac{1}{64} [/tex]
Answer:
The value of k is:
[tex]k = \frac{1}{64} [/tex]